Gestaltung hybrider Wertschöpfung und Arbeit im Kontext von Smart Services - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman; Frank, Maximilian; Schweppe, Thomans; Melzer, Annegret (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Strategie als Erfolgsfaktor - Koldewey, Christian; Dumitrescu, Roman (ServiceToday)

Development Process for Smart Service Strategies - Koldewey, Christian; Evers, Hans Heinrich; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Proceedings of The XXX ISPIM INNOVATION CONFERENCE)

Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)

Fault Tolerant and Fully Dynamic DFS in Undirected Graphs: Simple Yet Efficient - Baswana, Surender; Gupta, Shiv; Tulsyan, Ayush (44th International Symposium on Mathematical Foundations of Computer Science (MFCS 2019))

Grammatikwandel digital-kulturwissenschaftlich erforscht. Mittelniederdeutscher Sprachausbau im interdisziplinären Zugriff - Merten, Marie-Luis; Seemann, Nina; Wever, Marcel Dominik (Niederdeutsches Jahrbuch)

Approaches for Collaborative Security Defences in Multi Network Environments - Koning, Ralph; Polevoy, Gleb; Meijer, Lydia; de Laat, Cees; Grosso, Paola (2019 6th IEEE International Conference on Cyber Security and Cloud Computing (CSCloud)/ 2019 5th IEEE International Conference on Edge Computing and Scalable Cloud (EdgeCom))
Resolving distributed attacks benefits from collaboration between networks. We present three approaches for the same multi-domain defensive action that can be applied in such an alliance: 1) Counteract Everywhere, 2) Minimize Countermeasures, and 3) Minimize Propagation. First, we provide a formula to compute efficiency of a defense; then we use this formula to compute the efficiency of the approaches under various circumstances. Finally, we discuss how task execution order and timing influence defense efficiency. Our results show that the Minimize Propagation approach is the most efficient method when defending against the chosen attack.
Keywords: computer network security; multinetwork environments; multidomain defensive action; task execution order; timing influence defense efficiency; distributed attacks; collaborative security defence approach; minimize propagation approach; minimize countermeasure approach; counteract everywhere approach; Conferences; Cloud computing; Computer crime; Edge computing; Security; Defense Approaches; Multi-Domain Defense; Collaborative Defense; Defense Algorithms; Computer Networks

Lektionen für Alexa & Co?! - Haeb-Umbach, Reinhold (forschung)
Abstract Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Scalable Multi Objective Path Optimization for Multi-Laser Selective Laser Melting Scanning Systems - N., N.

Digitaler Wandel als strategischer Transformationsprozess – zum allgemeinen und hochschulspezifischen Verständnis der Digitalisierung - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie

Museum – Exhibition - Cultural Heritage. Museum – Ausstellung- Kulturelles Erbe. Changing Perspectives from China to Europe. Blickwechsel zwischen China und Europa - Seng, Eva- Maria

乌尔姆设计学院：20 世纪50 至60 年代联邦德国工业设计的训练中心 - The Ulm School of Design: A Training Center for Industrial Design in the Federal Republic of Germany in the 1950/60s - Seng, Eva- Maria (Zhuangshi 7)

包豪斯：20 世纪艺术、设计和建筑领域最具影响力的艺术学院 - Bauhaus: The Most Influential Art School in the Field of Arts, Design and Architecture in the 20th Century - Seng, Eva- Maria (Zhuangshi 11)

- “德国制造”——德意志制造联盟：20 世纪早期的德国工业设计、建筑设计与艺术院校改革 - ‘Made in Germany’- The German Werkbund: Industrial Design, Architecture and Art School Reform in the Early 20th Century - Seng, Eva- Maria (Zhuangshi 6)

The Museum - Seng, Eva- Maria (Tsinghua Art Museum TAM 11)

Geometrische Muster zwischen frühneuzeitlicher Utopie und russischer Avantgarde - Seng, Eva- Maria; Saage, Richard (Bauen mit Sinn. Schritte zu einer Philosophie der Architektur)

Kandidatur zum Bauhüttenwesen Die internationale für das immaterielle Kulturerbe der UNESCO - Seng, Eva- Maria („Genius loci“. Dombaumeistertagung Paderborn 23.-29. September 2018)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects Ottawa – Innovation for Local and Global Impact)

Kinder als Forscher in eigener und gemeinsamer Sache – ein Weg zur Partizipation? Ein kinderrechtebasierter didaktischer Ansatz und dessen Relevanz aus der Perspektive von Grundschulkindern - Hüpping, Birgit; Büker, Petra (Pädagogischer Blick)

Combining Children's Participation Rights in Research with Professionalisation of Educators and Teachers – Critical Analysis of a Transition Study Design - Büker, Petra (The Routledge International Handbook of Young Children’s Rights)

Kompetenzerwerb im Lese- und Literaturunterricht der Grundschule - Büker, Petra; Vorst, Claudia (Lese- und Literaturunterricht)
stark überarbeitete Auflage. (Deutschunterricht in Theorie und Praxis, Bd. 11/2). Baltmannsweiler: Schneider Verlag.

Partizipation von Kindergarten- und Grundschulkindern an Übergangsgestaltung, Übergangsforschung und am Transfer in optimierte Praxis: Erfahrungen aus der Kinderbefragungsstudie „buddY“. - Büker, Petra (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Children’s voices as a bridge between educators in kindergarten and teachers in primary school: Potential of children’s perspectives to support professional development - Büker, Petra; Höke, Julia (Listening to children’s advice about starting school and school age care. EECERA Book Series: Towards an Ethical Praxis in Early Childhood: From Research into Practice)

Big Data: Sublinear Algorithms for Distributed Data Streams - Malatyali, Manuel

Perspektiven des Transfers von Forschungsbefunden im Übergang Kindergarten-Grundschule - Büker, Petra; Müller, Ulrike Beate; Seifert, Anja; Arndt, Petra; Carle, Ursula; Graf, Ulrike; Kieferle, Christa; Kordulla, Agnes; Sturmhöfel, Nicole; Wehner, Franziska (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen

Grundthemen der Literaturwissenschaft: Literarische Institutionen

Zersetzung. Automatismen und Strukturauflösung
Erscheinungsjahr in Klammern: 2018

Die Explosion der Bilder im Kopf oder: „Les beaux livres sont écrits dans une sorte de langue étrangère.“ - Eke, Norbert Otto (Werner Fritsch: Faust Sonnengesang II und III. Materialien)

„Es ist nur eine Probe.“ George Taboris ‚musikalisches Opfer‘ „Die Goldberg-Variationen“ - Eke, Norbert Otto (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen biblischer Texte - Eke, Norbert Otto; Strotmann, Angelika (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Literarische Institutionen - Eke, Norbert Otto; Elit, Stefan (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Historischer Abriss: Aufklärung bis Gegenwart - Eke, Norbert Otto (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Zersetzung(en) dramatischer Ordnung: Marlene Streeruwitz und Rainald Goetz - Eke, Norbert Otto (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Zersetzung. Automatismen und Strukturauflösung - Eke, Norbert Otto; Hohlweck, Patrick (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Auslegungsmethode für zyklisch beanspruchte Stahl/CFK-Klebverbindungen unter besonderer Berücksichtigung des Rissfortschritts - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (19. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Design concept for adhesively bonded steel/CFRP structures under cyclic loading - Kowatz, Jannik; Meschut, Gerson (AJP2019 - 1st International Conference on Advanced Joining Processes - Book of Abstracts)

Approximate bound state solutions of the Klein-Gordon equation with the linear combination of Hulthén and Yukawa potentials - Ahmadov, A.I.; Aslanova, S.M.; Orujova, M.Sh.; Badalov, S.V.; Dong, Shi-Hai (Physics Letters A)

A possibilistic finite element method for sparse data - Dridger, A.; Caylak, Ismail; Mahnken, R.; Penner, Eduard (Safety and Reliability)

Stress-based fatigue life prediction of adhesively bonded hybrid hyperelastic joints under multiaxial stress conditions - Çavdar, Serkan; Teutenberg, Dominik; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B. (International Journal of Adhesion and Adhesives)

Development and qualification of a computer-aided method for the evaluation of failure modes in adhesively bonded joints - Ditz, Michael; Meschut, Gerson; Teutenberg, Dominik; Schwarze, T.; Smart, D. (The Journal of Adhesion)

Einfache Ermittlung von Schnellhärtungsparametern für elementar geklebte Strukturen - Ditter, Jan; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)

A test concept for bonded steel/CFRP structures - Meschut, Gerson; Teutenberg, Dominik; Wünsche, Marc (ADHESION ADHESIVES&SEALANTS)

SMS-WSJ: Database, performance measures, and baseline recipe for multi-channel source separation and recognition - Drude, Lukas; Heitkaemper, Jens; Boeddeker, Christoph; Haeb-Umbach, Reinhold (ArXiv e-prints)
We present a multi-channel database of overlapping speech for training, evaluation, and detailed analysis of source separation and extraction algorithms: SMS-WSJ -- Spatialized Multi-Speaker Wall Street Journal. It consists of artificially mixed speech taken from the WSJ database, but unlike earlier databases we consider all WSJ0+1 utterances and take care of strictly separating the speaker sets present in the training, validation and test sets. When spatializing the data we ensure a high degree of randomness w.r.t. room size, array center and rotation, as well as speaker position. Furthermore, this paper offers a critical assessment of recently proposed measures of source separation performance. Alongside the code to generate the database we provide a source separation baseline and a Kaldi recipe with competitive word error rates to provide common ground for evaluation.

Lektionen für Alexa und Co?! - Haeb-Umbach, Reinhold (DFG forschung 1/2019)
Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Structural Origins of Light-Induced Phase Segregation in Organic-Inorganic Halide Perovskite Photovoltaic Materials - Beal, Rachel E.; Hagström, Nanna Zhou; Barrier, Julien; Gold-Parker, Aryeh; Prasanna, Rohit; Bush, Kevin A.; Passarello, Donata; Schelhas, Laura T.; Brüning, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; McGehee, Michael D.; et al. (Matter)

Shedding X-ray Light on the Interfacial Electrochemistry of Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Shyam, Badri; Wang, Jiajun; Toney, Michael F.; Steinrück, Hans-Georg (Accounts of Chemical Research)

Morphology of Organic Semiconductors Electrically Doped from Solution Using Phosphomolybdic Acid - Huang, Tzu-Yen; Larrain, Felipe A.; Borca, Carlos H.; Fuentes-Hernandez, Canek; Yan, Hongping; Schneider, Sebastian Alexander; Chou, Wen-Fang; Rodriguez-Toro, Victor A.; Steinrück, Hans-Georg; Cao, Chuntian; Sherrill, C. David; Kippelen, Bernard; et al. (Chemistry of Materials)

Solid Electrolyte Interphase on Native Oxide-Terminated Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Abate, Iwnetim Iwnetu; Sivonxay, Eric; Shyam, Badri; Jia, Chunjing; Moritz, Brian; Devereaux, Thomas P.; Persson, Kristin A.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Modellbasierte IKT-Selektion für Methodentätigkeiten in der standortverteilten Produktentwicklung - Duehr, Katharina; Kampermann, Jonas; Taplick, Patrick; Gräßler, Iris; Albers, Albert (17. Gemeinsames Kolloquium Konstruktionstechnik: Agile Entwicklung physischer Produkte)
Durch die Globalisierung, den zunehmenden Wettbewerbsdruck sowie die wachsenden Kundenanforderungen setzen immer mehr Unternehmen auf die Vorteile global verteilter Entwicklungsnetzwerke. Die Verfügbarkeit neuer Technologien zur Unterstützung der standortverteilten Produktentwicklung treibt diese Entwicklung zusätzlich voran. Gepaart mit dem zunehmenden Auftreten agiler Ansätze führen die organisationalen Veränderungen zur steigenden Komplexität des Entwicklungsprozesses und fordern methodische Unterstützung. Die Vielzahl der verfügbaren Methoden sind jedoch bisher nur größtenteils auf die standortgebundene Anwendung ausgelegt. Der vorliegende Beitrag widmet sich daher der Erstellung eines Modells zur systematischen Unterstützung standortverteilter Methodenanwendung durch die Nutzung von Informations- und Kommunikationstechnologien.